Effective TME-related signature to predict prognosis of patients with head and neck squamous cell carcinoma - Wan, Lingfei; Li, Yuanshuai; Pan, Wenting; Yong, Yuting; Yang, Chao; Li, Chen; Zhao, Xingxing; Li, Ruihong; Yue, Wen; Yan, Xinlong (Frontiers in Molecular Biosciences, 2023)
The tumor microenvironment (TME) is crucial for the development of head and neck squamous cell carcinoma (HNSCC). However, the correlation of the characteristics of the TME appropriate and the prognostic of patients with HNSCC remains less known. In this study, we calculated the immune and stromal cell scores using the "estimate"R package. We identified seven new markers: FCGR3B, IGHV3-64, AC023449.2, IGKV1D-8, FCGR2A, WDFY4, and HBQ1. Subsequently, a risk model was constructed and all HNSCC samples were grouped into low-and high-risk groups. The results of both the Kaplan-Meier survival and receiver operating characteristic curve (ROC) analyses showed that the prognosis indicated by the model was accurate (0.758, 0.756, and 0.666 for 1-, 3and 5-y survival rates). In addition, we applied the CIBERSORT algorithm to reveal the significant differences in the infiltration levels of immune cells between the two risk groups. Overall, our study elucidated the roles of the TME and identified new prognostic biomarkers for patients with HNSCC.